Flight thrust performance of quadcopter / W. Kuntjoro...[et al.] - W., Kuntjoro; A. H. M., Saleh; R. E. M., Nasir; M. R., Abdullah*; M. G., Suada (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A quadcopter is a helicopter with four rotors. It is commonly used for small Unmanned Aerial Vehicles (UAV) because of its simple structure. Currently, quadcopters are mainly used in construction inspections, surveillance, search and rescue, and multimedia films. A study on the application of a stable quadcopter for its mapping properties is being held. A basic quadcopter purchased from market becomes the basis of the initial study. For starter, thrust behaviour of the copter needs to be investigated which is the aim of the study reported in this paper. The investigation was based on several experiments. Various parameters were recorded such as thrust, motor rpm, current load, power and speed. The quadcopter was tested with different payload in order to obtain its performance. From the static thrust tests, at maximum RPM of 100% throttle static thrust, the thrust recorded was 485 g per motor, with the maximum current load recorded was 7.0 A, and the maximum power was 77.7 W. The relationship between thrust against RPM and the thrust against power were shown in graphs.